1986
DOI: 10.1177/073346488600500208
|View full text |Cite
|
Sign up to set email alerts
|

Leisure Patterns and Attitudes of the Rural Elderly

Abstract: The purpose of the study was to ascertain the leisure practices and attitudes of a population of rural, midwestern elderly. Trained interviewers surveyed 3097 subjects in their homes. Data were analyzed at individual and activity cluster levels.Individual activity participation rates portrayed present subjects as regular gardeners, walkers, and media users. They also seemed to be fairly regular participants in games of chance. Those 75 years of age or older participated less than subjects 65-74 years old. Some… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
10
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 17 publications
5
10
0
Order By: Relevance
“…The influence of social expectations based on sex and functional competence, however, may be more pronounced. Furthermore, to be consistent with previous studies of adult leisure patterns, age is a primary factor with regard to pattern continuity and change over the adult life course and into very late life (Kelly, 1987;Mobily et al, 1986). Thus, this study was undertaken to examine leisure patterns of adults with mental retardation by ascertaining the relationship of age, sex, and functional competence (operationalized in the areas of motor and social-communication skills) to self-reported leisure activity participation, preferences, and interests.…”
supporting
confidence: 72%
See 3 more Smart Citations
“…The influence of social expectations based on sex and functional competence, however, may be more pronounced. Furthermore, to be consistent with previous studies of adult leisure patterns, age is a primary factor with regard to pattern continuity and change over the adult life course and into very late life (Kelly, 1987;Mobily et al, 1986). Thus, this study was undertaken to examine leisure patterns of adults with mental retardation by ascertaining the relationship of age, sex, and functional competence (operationalized in the areas of motor and social-communication skills) to self-reported leisure activity participation, preferences, and interests.…”
supporting
confidence: 72%
“…A review of the literature on leisure activity patterns of adult populations resulted in the generation of a list of activities, from which 50 were selected as being representative of those most commonly investigated (cf. Lawton, Moss, & Fulcomer, 1986Mobily et al, 1986;Riddick & Daniel, 1984;Tinsley, Teaff, Colbs, & Kaufman, 1985). A 20-item constraints scale modified from the work of McGuire (1979McGuire ( , 1984 completed the instrument.…”
Section: Instruments and Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…Mobily et al [17] had suggested that the elderly who live in rural environments are more actively engage in leisure activity and have a positive attitude compared to those in the urban environments. However, Wilcox et al [18] reported a contrary finding, in which there is no significant rural and urban difference among those who are actively involved in leisure.…”
Section: Sociodemographic Factors and Leisure Participation Among Eldmentioning
confidence: 99%